Piloting Implementation Design and Preliminary Readiness for Universal Suicide Risk Screening Program in Emergency Department of a Tertiary Care Centre, Nepal: A Mixed Method Study - Anmol Purna Shrestha; Roshana Shrestha; Renu Shakya; Pratiksha Paudel; Madeleine Sorenson; Amrita Gurung; Riya Bajracharya; Ajay Risal; Lakshmi Vijayakumar; Ashley Hagaman (Journal of Nepal Medical Association)
Introduction: Nearly three quarters of the suicides occur in developing world, however few evidenced-based health systems strategies exist to detect and prevent suicide in these contexts. This pilot study evaluates the feasibility of implementing a universal suicide risk screening program in a Nepalese emergency department. Methods: This study reports the preliminary training phases of a pilot implementation trial in the emergency department to evaluate the program. The approval was obtained from the Nepal Health Research Council (Approval no. 447/2021 P), and the Kathmandu University School of Medical Sciences Institutional Ethical Review Board (Approval no. 237/2021) and Yale University IRB (Protocol ID 2000029480). Implementation assessments included suicide screening acceptability, appropriateness, confidence, system priority, and myth knowledge of staff. Implementation strategies were selected, decolonized, and preliminarily trained followed by phased supportive coaching to initiate the screening package. We designed the implementation package through co-design staff focus groups and embedded ethnography. Results: Co-design focus groups (n=8) occurred with staff and leadership. We trained 26 (76.47%) the staff on the Nepali suicide screening tool followed by supported phased initial screening over two months. Implementation assessments demonstrated increased scores on appropriateness, confidence, system priority, and myth knowledge. The implementation package included key strategies to be deployed over six months. The embedded ethnographic observations revealed barriers to effective implementation, such as anticipated stigma, reluctance to engage families, and distrust in referral processes. Conclusions: The pilot study demonstrated that training improves staff appropriateness, confidence, system priority, and myth knowledge. Despite initial barriers, co-designed strategies and phased coaching facilitates screening uptake, highlighting the program's potential for sustainable implementation.